Don’t Stop Thinking about Yesterday – Why There Was No Indigenous Counterpart to Intellectual Property Law in Imperial China - Alford, William P. (Columbia Journal of Asian Law, 1993)
The notion that copyright arose soon after the advent of printing enjoys wide currency in the scholarly world. Chinese historians date copyright from the rise of printing during the Tang Dynasty (A.D. 617- 906), while Western theorists of economic development contend that the inexpensive dissemination of texts necessitated the formal legal protection that copyright is intended to provide. In short, the accepted wisdom among “intellectual property scholars . . . [is] that copyright emerged with the invention of printing,” as Zheng Chengsi and Michael Pendleton declare in their recent monograph on copyright in the People’s Republic of China (PRC). This essay takes issue with the accepted wisdom, at least as concerns imperial China. After first endeavoring to delineate an appropriate scope for inquiring into imperial Chinese legal history, this essay considers whether there was indigenous formal legal protection for intellectual property in China prior to the twentieth century introduction of Western notions of such law. It finds evidence of restrictions on the unauthorized reproduction of certain books, symbols and products but determines that it would be erroneous to see these as constituting what we in the United States now typically understand intellectual property to be, for they were little concerned with the protection of property or other private interests. Their real purpose was the maintenance of imperial legitimacy and power. Accordingly, this essay turns in its final section to a consideration of Chinese political culture and, particularly, its engagement with the past in the effort to illuminate why China did not respond to the introduction of printing and other major technological advances in the manner that both Chinese and Western scholars would have us believe.